2005
DOI: 10.1002/ejic.200500567
|View full text |Cite
|
Sign up to set email alerts
|

Mixed‐Ligand Copper Complexes with 8‐Methylthioquinoline and Triphenylphosphane or theo‐Semiquinone/Catecholate Redox System

Abstract: The complex [Cu(MTQ)(PPh3)2](BF4), MTQ = 8‐methylthioquinoline, exhibits distorted tetrahedral coordination at thecopper(I) center. One of two crystallographically independent molecules found in the unit cell exhibits a more pronounced inclination towards a (3+1) coordination arrangement. In comparison to the analogous complex with the related imine/thioether chelate ligand 1‐methyl‐2‐(methylthiomethyl)‐1H‐benzimidazole, the cation [Cu(MTQ)(PPh3)2]+ shows stronger bonding of CuI to S and weaker interaction wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
2
11
0
1
Order By: Relevance
“…The small magnitude of the thermodynamic parameters for [Cu Sal ] + in comparison to those reported for many metal–dioxolene systems10 is consistent with the relatively minor predicted change in bond lengths accompanying the shift in the locus of oxidation for [Cu Sal ] + . While temperature-dependent valence tautomerism between Cu(II)–catecholate and Cu(I)–semiquinonate species has been reported,70,72 this is the first account of a spin equilibrium involving a Cu–phenoxide complex. Interestingly, in the case of [Ni Sal ] + , the shift in the locus of oxidation from the ligand to the metal is due to large changes in the ligand field associated with axial ligation at low temperature 18.…”
Section: Discussionmentioning
confidence: 76%
“…The small magnitude of the thermodynamic parameters for [Cu Sal ] + in comparison to those reported for many metal–dioxolene systems10 is consistent with the relatively minor predicted change in bond lengths accompanying the shift in the locus of oxidation for [Cu Sal ] + . While temperature-dependent valence tautomerism between Cu(II)–catecholate and Cu(I)–semiquinonate species has been reported,70,72 this is the first account of a spin equilibrium involving a Cu–phenoxide complex. Interestingly, in the case of [Ni Sal ] + , the shift in the locus of oxidation from the ligand to the metal is due to large changes in the ligand field associated with axial ligation at low temperature 18.…”
Section: Discussionmentioning
confidence: 76%
“…On the other side, Kaim et al,570 have also reported the use of a weak π ‐acceptor thioether to induce sensitive valence tautomerism in paramagnetic copper complexes related to amine oxidase enzymes. In a more recent study, the comparison between two thioether ligands that differ on their π ‐acceptor capacity and structural rigidity has been used to have a comparative study of both effects 571…”
Section: Switching Materialsmentioning
confidence: 99%
“…In contrast, above 250 K, the EPR signal of [Cu I (mmb)(3,5‐dbsq)] starts to appear, and it dominates above 350 K. The compounds [Cu I (dde)(3,5‐dbsq)]/[Cu II (dde)(3,5‐dbcat)] (dde=1‐diphenylphosphino‐2‐dimethylaminoethane) and [Cu I (mtq)(3,5‐dbsq)]/[Cu II (mtq)(3,5‐dbcat)] (mtq=8‐methylthioquinoline) also exhibit valence tautomerism 77. 78 Valence tautomerism of copper can also be observed in enzymes that play an important role in the oxidation of amines 79. Hence, the study of Cu valence‐tautomeric systems is important from biological and biomimetic viewpoints, as well as for basic science.…”
Section: Valence Tautomerismmentioning
confidence: 99%